Analisis Dampak Likuiditas, Leverage, Firm Size, dan Kebijakan Dividen Terhadap Kinerja Keuangan Pada Perusahaan Pertambangan Yang Terdaftar di Bei Pada Periode Tahun 2020-2024 - Khotimah, Qory Husnul; Parhusip, Austin Alexander (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Financial performance is a measure used to assess a company's ability to generate profits. Increasing ROA indicates improved performance. This study aims to determine whether Liquidity, Leverage, Firm Size, and Dividend Policy have a partial or simultaneous effect on financial performance in mining companies listed on the Indonesia Stock Exchange in 2020-2024. The study employed quantitative research with an associative approach. The population of this study was 75 mining companies listed on the IDX, while the sample size was 8 companies using a purposive sampling technique. Observations were conducted over a five-year period, from 2020 to 2024. This study employed multiple linear regression analysis, classical assumption tests, hypothesis tests, and coefficient of determination tests using SPSS 25.0 software. The partial analysis results showed that Liquidity, Leverage, Firm Size, and Dividend Policy had no effect on Financial Performance. Simultaneous analysis results indicated that Liquidity, Leverage, Firm Size, and Dividend Policy had no effect on Financial Performance.